Hollywood 1938 : motion pictures' greatest year - Jurca, Catherine, 1964- (Berkeley : University of California Press, 2012)
N Hollywood 1938, Catherine Jurca brings to light a tumultuous year of crisis that has been neglected in histories of the studio era. With attendance in decline, negative publicity about stars that were "poison at the box office," and a spate of bad films, industry executives decided that the public was fed up with the movies. Jurca describes their desperate attempt to win back audiences by launching Motion Pictures' Greatest Year, a massive, and unsuccessful, public relations campaign conducted in theaters and newspapers across North America. Drawing on the records of studio personnel, independent exhibitors, moviegoers, and the motion pictures themselves, she analyzes what was wrong-and right-with Hollywood at the end of a heralded decade, and how the industry's troubles changed the making and marketing of films in 1938 and beyond.
Introduction: Hollywood looks at its audience -- The campaign. Annus horribilis -- Goldwyn's folly -- Such a thing as bad publicity -- The moviegoing habit -- Exhibitors, the movie quiz contest, and a divided industry. The minds of exhibitors -- The carrot and the stick -- The quiz contest on the ground -- What the contest did for me -- Independents rebel -- The campaign and the press. The film industry speaks its mind -- Marginal moviegoers -- The gossip columnists -- The dailies have their say -- The films. "The finest array of productions" -- Ninety-four films -- The death of glamour -- Human films -- The human side of screwball -- You can't take it with you -- Four daughters -- Boys town -- Marie Antoinette -- That's entertainment -- The fourth estate -- Conclusion: motion pictures' worst year.
"Portions of this book appeared as "What the Public Wanted: Hollywood, 1937-1942," Cinema Journal 47, no. 2 (2008): 3-25; and "Motion Pictures' Greatest Year (1938): Public Relations and the American Film Industry," Film History 20, no. 3 (2008): 344-56"--Title page verso.
Includes bibliographical references (pages 231-261), index and filmography.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Motion pictures -- California -- Los Angeles -- History -- 20th century; Motion picture audiences -- United States -- History; Motion picture industry -- Economic aspects -- California -- Los Angeles -- History -- 20th century; Hollywood (Los Angeles, Calif.) -- History -- 20th century; Cinéma -- Californie -- Los Angeles -- Histoire -- 20e siècle.; Cinéma -- Publics -- États-Unis -- Histoire; Cinéma -- Industrie -- Aspect économique -- Californie -- Los Angeles -- Histoire -- 20e siècle.; PERFORMING ARTS -- Film & Video -- General; Motion picture audiences; Motion picture industry -- Economic aspects; Motion pictures; California -- Los Angeles; California -- Los Angeles -- Hollywood; United States; Music, Dance, Drama & Film; Film; 1900-1999; History